Peran Akuntansi Sektor Publik dalam Perencanaan Anggaran pada Kinerja Keuangan Daerah Kota Depok Tahun 2022 - Inayah Putri Kurniati; Sonny Fransisco Siboro; May Angeli; M. Adnan Vero W. (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the role of public sector accounting in regional financial performance budget planning in Depok City. The research used qualitative methods, the results obtained in this research were that the regional financial performance of Depok City experienced an increase in the realization of regional income in 2022.